Religious Voting Blocs in the 1992 Election: The Year of the Evangelical? - Kellstedt, Lyman A. (Sociology of religion, 1994)
This article examines the political alignment and voting behavior of major American religious traditions in 1992. We discover that evangelical Protestants solidified their growing Republican proclivities of recent decades, becoming a core voting bloc within the GOP coalition. Mainline Protestants , traditionally at the center of the Republican party, deserted President Bush in large numbers for Clinton and Perot, while many Catholic voters returned to their former Democratic allegiance. The expanding bloc of secular voters provided strong additional support for Democratic candidates and liberal policies. In conclusion, we speculate on the emergence of a different kind of ethnoreligious alignment in electoral politics.